2013
DOI: 10.1007/s00394-013-0637-0
|View full text |Cite
|
Sign up to set email alerts
|

Diets high in total antioxidant capacity improve risk biomarkers of cardiovascular disease: a 9-month observational study among overweight/obese postmenopausal women

Abstract: Findings suggest that consumption of diets high in TAC are inversely associated with plasma CRP levels cross-sectionally and dynamically and may contribute to CVD protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Several studies demonstrate that higher TAC from diet and supplements beneficially alters lipid and glucose profiles [30, 31], improves endothelial function [32], and reduces systemic inflammation [33]. Recent clinical studies have shown that higher TAC from diet and supplements can be associated with a decrease in inflammatory markers in overweight/obese postmenopausal women [34]. Supplements in this study largely contributed to the TAC value.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies demonstrate that higher TAC from diet and supplements beneficially alters lipid and glucose profiles [30, 31], improves endothelial function [32], and reduces systemic inflammation [33]. Recent clinical studies have shown that higher TAC from diet and supplements can be associated with a decrease in inflammatory markers in overweight/obese postmenopausal women [34]. Supplements in this study largely contributed to the TAC value.…”
Section: Discussionmentioning
confidence: 67%
“…[24] showed that dietary total antioxidant capacity was associated with lower serum CRP concentrations in young Japanese women (474 women, aged 18-22 years) regardless of assay used to measure it. Also, in a 9-month observational study among postmenopausal women, Wang and his colleagues showed that consumption of diets rich in total antioxidants was associated with lower plasma CRP levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has documented the baseline dietary TAC of U.S. adults from NHANES 2001–2002 by combining the USDA flavonoid, proanthocyanidins, and supplement databases [ 19 ]. We found that TAC from both diet and supplements was associated with decreased serum C-reactive protein (CRP) and plasma homocysteine [ 20 , 21 ], implying potential applicability of TAC in predicting CVD risk.…”
Section: Introductionmentioning
confidence: 99%